Improving The Quality of Village Development Planning Through Training on the Preparation of Government Work Plans and Budget for Ulak Kembahang II - Mardalena Mardalena; Didik Susetyo; Siti Rohima; Imelda Imelda; Harunnurasyid Harunnurasyid; Rahma Nida (LPPM UIKA Bogor, 2022)
Development planning is a stage of activities organized by the village government by involving the community in the utilization and allocation of village resources in order to improve the quality of human life. The direction of village development must be oriented towards increasing the welfare of the village community and based on the applicable laws and regulations. The preparation of development planning documents must contain the aspirations of the village community and be in accordance with village conditions. The problem that occurs in Ulak Kembahang II Village is that they still do not understand the importance of preparing the RKPDes (Village Government Work Plan) and APBDes (Village Budget) due to limited information, level of knowledge, and skills in compiling these documents. Therefore, the purpose of this community service activity is to carry out mentoring and training for village officials and elements of the village community in order to increase knowledge and skills in the process of preparing the RKPDes and APBDes documents and be able to compile these documents independently and actively participate in accordance with laws and regulations applicable. The results of the evaluation of this community service activity showed an increase in understanding and knowledge about the mechanism for preparing the RKPDes and APBDes documents by 28 community service participants consisting of village officials, community elements, youth organizations, BPD, BUMDes management, and PKK administrators with an average level of understanding an average of 86.4 percent.